Toxicity and toxins of natural blooms and isolated strains of Microcystis spp. (Cyanobacteria) and improved procedure for purification of cultures. - Shirai, M (1991)
All samples of cyanobacterial blooms collected from 1986 to 1989 from Lake Kasumigaura, Ibaraki Prefecture, Japan, were hepatotoxic. The 50% lethal doses (LD50s) of the blooms to mice ranged from 76 to 556 mg/kg of body weight. Sixty-eight Microcystis cell clones (67 Microcystis aeruginosa and 1 M. viridis) were isolated from the blooms. Twenty-three strains (including the M. viridis strain) were toxic. However, the ratio of toxic to nontoxic strains among the blooms varied (6 to 86%). Microcystins were examined in six toxic strains. Five toxic strains produced microcystin-RR, -YR, and -LR, with RR being the dominant toxin in these strains. Another strain produced 7-desmethylmicrocystin-LR and an unknown microcystin. This strain showed the highest toxicity. Establishment of axenic strains from the Microcystis cells exhibiting extracellularly mucilaginous materials was successful by using a combination of the agar plate technique and two-step centrifugation.